PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KERAMIK PORSELIN DAN KACA LISTING DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Akbar Malik; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This Study aims to determinate the effect capital structure and Profitability on on the value of the company on ceramic porcelain and glass companies listing on the Indonesia Stock Exchange period 2009-2014 .The capital structure is used as independent variables with indicator Debt to Assets Ratio (DAR), Longterm Debt to Equity Ratio ( LDER), and Profitability with indicator Return On Equity (ROE), and Return On Investment (ROI). While that is used as the dependent variable is value of the company is Price Earning Ratio (PER).This Study uses secondary data from the financial statements of companies ceramic porcelain and glass companies listing on the Indonesia Stock Exchange period 2009-2014. Sampling is done by purposive sampling that used is 5 ceramic company of porcelain and glass.Technic Analysis using the simple linear regression analysis, multiple linear regression analysis, test the coefficient of determination, t test and f test. Analysis of data using linear regression analysis with SPSS 21.The Result Shower that the variables ROI partially (t test) affect the value of the company on Ceramic Porcelain and Glass company listed on Indonesia Stock Exchange (IDX), while the variable DAR, LDER, and ROE, ider no effect on the Value of Company on Ceramic Porcelain and Glass company listed on Indonesia Stock Exchange (IDX). The Result of the study simultaneously (f test) showed a significant effect of the variable DAR, LDER, ROE, and ROI ider on firm value on Ceramic Porcelain and Glass company listed on Indonesia Stock Exchange (IDX).Keyword: Capital Structure, Profitability, Corporate Values, DAR, LDER, ROE, ROI